The breakthrough : human rights in the 1970s - Eckel, Jan; Moyn, Samuel (Pennsylvania studies in human rights., 2014)
Between the 1960s and the 1980s, the human rights movement achieved unprecedented global prominence. Amnesty International attained striking visibility with its Campaign Against Torture; Soviet dissidents attracted a worldwide audience for their heroism in facing down a totalitarian state; the Helsinki Accords were signed, incorporating a "third basket" of human rights principles; and the Carter administration formally gave the United States a human rights policy. This book examines this decisive era as a whole, tracing key developments in both Western and non-Western engagement with human rights and placing new emphasis on the role of human rights in the international history of the past century. -- Jacket description.